Exploring experience of Iranian medical sciences educators about Best Evidence Medical Education: A content analysis - Seyed Amir Hossein Emami; Hamidreza Khankeh; Maryam Karbasi Motlagh; Nazila Zarghi; Mandana Shirazi (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND AND OBJECTIVE: Applying the Best Evidence Medical Education (BEME) in real educational arena is a necessity in medical education. As to the literature, there are enough evidence; however, their application by educators and policymakers has been still failed. Therefore, this study conducted to explore the experience of educators about applying BEME in Iranian context. MATERIALS AND METHODS: Qualitative approach using content analysis method was utilized for exploring 25 participants involved with medical education in different levels, introduced the study using purposeful sampling. Data were collected through a semi-structured interview by which they answered to researcher's questions in around 45 min about how they apply evidence in their educational setting. To make more clarification, probing questions were used. Interviews were recorded and transcribed and then analyzed by coding paradigm immediately. RESULTS: Three categories were emerged as: applying different levels of evidence, substitution of evidence-based medicine for BEME, and variation of understanding BEME. The first category includes subcategories of using personal experience, textbooks, and filtered papers. The second contains lack of knowledge about BEME elements, time and motivation as well as no priority for applying available medical education evidence; and third, using different terminology and having some problems in applying process, based on individual understanding and using papers with or without modification. DISCUSSION: For effective evidence application, it is necessary to operationalize BEME terminology and overcome any ambiguity surrounded it. It is also important to suggest educators to apply the appraised evidence as well as teach them how they search and appraise evidence independently. Certainly, in the first steps, supervision and providing a proper context for BEME applications are crucial.